Application Of Work Discipline To Employees Work Productivity At Ninja Express Lengkong Branch - RR Dewi Pratiwy Sugiharty; Muhammad Sugiharto (Sean Institute, 2024)
This research aims to reveal the impact of the level of discipline on employee work productivity at Ninja Express. Employee productivity is the key for a company to achieve its business goals. Work discipline shows a person's ability to obey rules, maintain focus, and be consistent in work. The research method used is descriptive qualitative with data collection through interviews and observation. The research results show that the Ninja Express branch in Lengkong has implemented various types of work discipline and paid attention to factors such as leadership, organizational culture, reward and punishment systems, as well as working conditions that support productivity and the achievement of company goals. The conclusion of this research is that work discipline has a significant influence on employee work productivity.